TRADISI DANDANGAN SEBAGAI KAJIAN PEMBELAJARAN DALAM MENDUKUNG PENCAPAIAN VISI UNIVERSITAS KEBUDAYAAN (Studi pada Mata Kuliah Konsep Ilmu Pengetahuan Sosial) - Erik Aditia Ismaya; Santoso Santoso (Universitas Muria Kudus, 2019)
The purpose of this study is to analyze the Dandangan Tradition while simultaneously analyzing the meaning and value of the Dandangan Tradition as a study of learning in supporting the achievement of the vision of the University of Culture. This study uses qualitative descriptive research and field studies. The main data obtained directly through interviews with informants. observation, literature study and documentation.. The validity of the source triangulation technique is used. Data analysis was performed through inductive-descriptive-verivative analysis. The results of the study showed the Dalih Tradition from the sound of drum beating. The sound of the drum that reads